Humor and violence : seeing Europeans in Central African art - Strother, Z. S. (African expressive cultures, 2016)
"Humor and Violence examines the rich history of portraying Europeans in Central African art in images ranging from heart-wrenching scenes of human trafficking to playful parodies of colonialists. Z. S. Strother contends that the dialectic of humor and violence reveals deep insights into the psychology of power and resistance that continues to operate in the region today. Her argument is built on a set of works of art and demonstrates the important role that patronage and political and social history played in their creation. Strother conveys Central African ideas about how the therapeutic power of humor can initiate social change and upset power relations between oppressors and oppressed. This analysis plunges seemingly benign figures into a maelstrom of violence and crime -- rape, murder, torture, and forced labor on a massive scale. By restoring the dialectic of humor, this study reveals the complicated psychological codependency of Africans and Europeans over a long period of history and maintains that art plays a mediating function in the mechanics and ethics of power."--Front cover flap